Bóle brzucha u dzieci – diagnostyka różnicowa i postępowanie terapeutyczne w POZ - Grata-Borkowska, Urszula; Pokorna-Kałwak, Dagmara; Mastalerz-Migas, Agnieszka (Lekarz POZ, 2016)
Abdominal pain is among the most common reasons for pediatric emergency department visits, and for the family practice visits, too. There are acute and chronic abdominal symptoms and organic, functional and psychogenic abdominal pain. There is continuous and paroxysmal abdominal pain. The most often abdominal pain by children we can distinguish functional abdominal pain. The causes depend on age of children; appendicitis is the most often abdominal acute pain in children above 12 years. Each child with acute abdominal pain should be examed immediately by general practitioner. Acute abdominal pain is almost always a symptom of a serious disease and it may be indicator of the need for surgery.